Corn and rice starch-based bio-plastics as alternative packaging materials - Marichelvam, Mariappan Kadarkarainadar; Jawaid, Mohammad; Khan, Mohammad Asim (MDPI, 2019)
Due to the negative environmental impacts of synthetic plastics, the development of biodegradable plastics for both industrial and commercial applications is essential today. Researchers have developed various starch-based composites for different applications. The present work investigates the corn and rice starch-based bioplastics for packaging applications. Various samples of bioplastics are produced, with different compositions of corn and rice starch, glycerol, citric acid, and gelatin. The tensile properties were improved after adding rice starch. However, water absorption and water solubility were reduced. On the basis of these results, the best sample was analyzed for thickness testing, biodegradability properties, SEM, hydrophilicity, thermogravimetric analysis, and sealing properties of bioplastic. The results show the suitability of rice and corn-based thermoplastic starch for packaging applications.